(3GdSja GdeSdhd Ydi ef dYfg GdQShds - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg hYdi Bdg hUMHg hef hGdGg CeG HYO agPg QSGdI CPcQ ajgG eG JjSQ ef CTjGA hQOJ ai CMGOjK dYfgG djLJfHgG ef hba YdjgG s
(3BNQgG (B:s
(3hdYf YHO GdOjfGQ hGdOQge hdYfJ GdbOQjI CiGdPjf jVjahf CaYGd GdYHGO Edi bOQge hdh PcQJ dc CMGOjKgG dWGd GdcdGe hGdebUhO GdGNJUGQ hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdeDda ef JdGejP GdYdGeI GdLhgQis
(3Jcde ajgG GdeDda Ydi ef jLhR dYfges
(3HChdg fbd Yf eYfi GddYf ai GddZIs
(3HgG fXGe GdJYbjHI JGQjN s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
Keywords: (3GdeLGejYs